Penyalahgunaan Teknologi Deepfake untuk Konten Pornografi Non-Konsesual di Indonesia - Cerens Amanda Gea Pitaloka (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
The development of digital technology, particularly deepfake, has brought negative impacts, including the protection against non-consensual pornography content. Deepfake, which uses artificial intelligence to manipulate images, videos, or audio, allows the creation of pornography without the consent of the individual whose face or identity is manipulated. This phenomenon results in violations of privacy, honor, and the psychological well-being of the victims, while also spreading false information that can damage public perception. Although Indonesia has regulations such as Law No. 11 of 2008 on Electronic Information and Transactions (ITE Law) and Law No. 44 of 2008 on Pornography, there are no specific provisions regulating the use of deepfake technology. This article identifies deficiencies in existing regulations and provides recommendations for adaptive legal measures, including legislative updates, strengthening digital platform responsibilities, enhancing law enforcement capacity, and international cooperation to address this threat. It is hoped that with these measures, protection for individuals in the digital era can be strengthened.